2022
DOI: 10.3390/jcm11133888
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Molecular Biomarkers in Ovarian Cancer Using the Gene Expression Profile

Abstract: Ovarian cancer is a common cause of death among women worldwide. The current diagnostic and prognostic procedures available for the treatment of ovarian cancer are either not specific or are very expensive. Gene expression profiling has proved to be a very effective tool in the exploration of new molecular markers in patients with ovarian cancer, although the link between such markers and patient survival and clinical outcomes is still elusive. We are looking for genes that may function in the development and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
3
5
0
Order By: Relevance
“…Changes in tumor suppressor gene expression, proto-oncogenes, pro-apoptotic genes, genes related to chromatin remodeling and genes related to carcinogenesis were observed. However, the relationship between these markers and patient survival and clinical outcomes was not observed (40). Another study evaluating the relationship between human epidermal growth factor receptor and clinicopathological characteristics of epithelial ovarian cancer showed that HER2/neu was positive in a quarter of patients, which is significantly associated with cancer marker CA 125 before treatment.…”
Section: Common Genes Involved In Ovarian Cancer Breast and Polycysti...mentioning
confidence: 99%
“…Changes in tumor suppressor gene expression, proto-oncogenes, pro-apoptotic genes, genes related to chromatin remodeling and genes related to carcinogenesis were observed. However, the relationship between these markers and patient survival and clinical outcomes was not observed (40). Another study evaluating the relationship between human epidermal growth factor receptor and clinicopathological characteristics of epithelial ovarian cancer showed that HER2/neu was positive in a quarter of patients, which is significantly associated with cancer marker CA 125 before treatment.…”
Section: Common Genes Involved In Ovarian Cancer Breast and Polycysti...mentioning
confidence: 99%
“…Epidermal growth factor receptor (EGFR) is often upregulated in OC, conveying a proliferative advantage to these tumors [43,44]. In vitamin D-sensitive OC cells, 1,25D3 downregulated EGFR expression, reducing their proliferative potential [41].…”
Section: Effect Of 125d3 and Its Analogs On Proliferative Signalsmentioning
confidence: 99%
“…From 1990 to 2019, the net drift rate of ovarian cancer as a cause of death in China was 0.76% (95% CI 0.57–0.95) per year [ 6 ]. A lack of visible clinical manifestations during the early stages of the disease [ 1 , 5 , 7 ] means that ovarian cancer is often not detected early with non-invasive methods, and thus most individuals who are diagnosed with the disease are already in the mid to late stages. As there are few treatment options that can improve the prognosis of ovarian cancer patients, most patients eventually die from the disease due to disease recurrence and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…It would be incredibly useful for ovarian cancer management to have biomarkers that could reliably predict a patient’s outcome [ 7 , 8 ]. As a heterogeneous disease, ovarian cancer contains several distinct subtypes that involve heterogeneous populations of cells and proteins [ 2 , 9 ].…”
Section: Introductionmentioning
confidence: 99%